RISK MANAGEMENT AND INVESTMENT DECISION-MAKING: A COMPREHENSIVE REVIEW OF THEIR IMPACT ON OPERATIONAL PERFORMANCE AND SUSTAINABILITY - Ahmad Yani, Yogi; Yani, Ahmad; Novia (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2025)
In a dynamic and uncertain global business landscape, risk management and investment decision-making have become fundamental pillars for optimal operational performance and corporate sustainability. This study comprehensively analyzes existing literature to construct an understanding of how the integration of these two disciplines affects operational performance and sustainability, as well as identifying trends, challenges, and research gaps. This research uses a comprehensive literature review approach, identifying, analyzing, and synthesizing reputable scientific journal articles, industry reports, and other relevant publications from 2020 to 2025. Data was collected through systematic searches of academic databases using keywords related to risk management, investment, operational performance, and sustainability. The analysis was conducted through thematic and narrative synthesis to identify patterns, gaps, and best practice recommendations. The results of the study show that risk management plays a crucial role in investment decision-making, directly affecting profitability and operational efficiency. The integration of Environmental, Social, and Governance (ESG) principles into risk management and investment is increasingly important to promote corporate sustainability, where effective risk management can influence investment choices and contribute to stronger financial performance. Despite positive trends in the growth of the risk management and sustainable investment market in Southeast Asia, significant challenges remain, including a lack of ESG standardization and reporting, as well as complex cyber risk and human resource risk management. Effective integration between risk management and investment decision-making is essential for operational performance and long-term sustainability. However, challenges related to standardization and reporting require collaborative efforts from policymakers, practitioners, and academics. Suggestions for future research include studies that quantify the specific impact of integrating risk management and sustainable investment on operational and sustainability performance metrics across various sectors, particularly in emerging markets such as the property sector in Indonesia, with a focus on climate risk and digitalization.